Kant on Radical Evil - (:unkn) unknown (My University, 2015)
The purpose of this thesis is to propose an interpretation of Kant’s claim that the human being’s evil nature is the effect of the free power of choice. I suggest that if his concept of free choice is properly understood, Kant’s claim should be interpreted as follows: the human being’s radical evil is the effect of a failure to use freely the power of choice that determines its fundamental disposition, a failure that is to be presupposed as universal for all human agents. According to this reading, we are evil by nature since evil lies in our fundamental disposition. Still, our evil nature can be thought of as acquired, since we could constitute our fundamental disposition as morally good through freedom of choice. In the end, it turn out that for Kant, the concepts of free choice and of evil nature are closely connected.
Keywords: Ethics; Evil; Kant; Moral Psychology; Philosophy of Action